Facilitated Transport Membranes With Ionic Liquids for CO2 Separations - Klemm, Aidan; Lee, Yun-Yang; Mao, Hongchao; Gurkan, Burcu (Frontiers in Chemistry, 2020)
In recent years, significant development milestones have been reached in the areas of facilitated transport membranes and ionic liquids for CO2 separations; making the combination of these materials an incredibly promising technology platform for gas treatment processes, such as post-combustion and direct CO2 capture from air in buildings, submarines, and spacecrafts. The developments in facilitated transport membranes involve consistently surpassing the Robeson upper bound for dense polymer membranes, demonstrating a high CO2 flux across the membrane while maintaining very high selectivity. This mini review focuses on the recent developments of facilitated transport membranes, in particular discussing the challenges and opportunities associated with the incorporation of ionic liquids as fixed and mobile-carriers for separations of CO2 at low partial pressures (< 1 atm).